TorsinA restoration in a mouse model identifies a critical therapeutic window for DYT1 dystonia - Li, Jay (J Clin Invest, 2021)
In inherited neurodevelopmental diseases, pathogenic processes unique to critical periods during early brain development may preclude the effectiveness of gene modification therapies applied later in life. We explored this question in a mouse model of DYT1 dystonia, a neurodevelopmental disease caused by a loss-of-function mutation in the TOR1A gene encoding torsinA. To define the temporal requirements for torsinA in normal motor function and gene replacement therapy, we developed a mouse line enabling spatiotemporal control of the endogenous torsinA allele. Suppressing torsinA during embryogenesis caused dystonia-mimicking behavioral and neuropathological phenotypes. Suppressing torsinA during adulthood, however, elicited no discernible abnormalities, establishing an essential requirement for torsinA during a developmental critical period. The developing CNS exhibited a parallel “therapeutic critical period” for torsinA repletion. Although restoring torsinA in juvenile DYT1 mice rescued motor phenotypes, there was no benefit from adult torsinA repletion. These data establish a unique requirement for torsinA in the developing nervous system and demonstrate that the critical period genetic insult provokes permanent pathophysiology mechanistically delinked from torsinA function. These findings imply that to be effective, torsinA-based therapeutic strategies must be employed early in the course of DYT1 dystonia.